185P Safety, tolerability, and antitumor activity of trastuzumab deruxtecan (T-DXd) in patients (pts) with HER2+ metastatic breast cancer (mBC) and active brain metastases (BM) in DESTINY-Breast07 (DB-07) - C. Anders; S. Loi; Erika Hamilton; Komal Jhaveri; P. Schmid; Erhan Gökmen; S-A. Im; Cengiz Karaçin; Carlos H. Barrios; Y.H. Park; S. Uzunoğlu; Sarah E. Boston; et al. (2024)
DEBBRAH, ROSET-BM, TUXEDO-1, and a pooled DB-01, -02, -03 analysis indicate robust efficacy of T-DXd in pts with stable/active BM; however, efficacy in pts with BM is not yet fully established. DB-07 is a phase Ib/II, multicenter, open-label study exploring the safety, tolerability, and antitumor activity of T-DXd alone or in combination with other anticancer agents (NCT04538742). Results are from an interim analysis of the dose-expansion phase of T-DXd monotherapy in pts with active BM. Pts had locally assessed HER2+ mBC with measurable disease. No or one prior line of therapy for mBC was allowed; a disease-free interval of ≥12 months from (neo)adjuvant HER2-directed therapy or chemotherapy was required. Pts had untreated BM not requiring local therapy or progressing BM after treatment with local therapy. Ongoing use of systemic corticosteroids (>2 mg dexamethasone daily or equivalent) for control of BM symptoms was exclusionary. Pts received T-DXd 5.4 mg/kg intravenously every 3 weeks. Primary endpoints were safety and tolerability; secondary endpoints included objective response rate (ORR) and progression-free survival (PFS) per RECIST 1.1 and Response Assessment in Neuro-Oncology (RANO)-BM. Thirty-five pts with active BM were treated (median age 49 years); median follow up was 11.5 months (range 5.3–24.6). As of August 1, 2023, the most common any-grade adverse events (AEs) were nausea (74.3%; Grade 3, 5.7%) and vomiting (45.7%; Grade 3, 2.9%); no Grade ≥4 nausea or vomiting was reported. By RANO-BM, confirmed ORR was 57.1% and PFS rate at 12 months was 74.6% (Table). The safety profile is consistent with the known profile for T-DXd and data confirm promising efficacy in pts with active BM; a median PFS has not been reached after 11.5 months. Ongoing analyses will provide more mature data.Table: 185PKey safety and efficacy dataT-DXd in pts with active BM (n=35)Any-grade AEs, n (%)35 (100)AEs Grade ≥3, n (%)18 (51.4)Serious AEs, n (%)5 (14.3)Any-grade pneumonitis (adjudicated as interstitial lung disease related to study drug), n (%)3 (8.6)Grade 2, n (%)2 (5.7)Grade 5, n (%)1 (2.9)Median actual treatment duration, months (range)10.0 (2.6–24.3)Overall response (RECIST 1.1 by investigator)Intracranial response (RANO-BM BICR)Confirmed ORR, % (80% CI)77.1 (65.5, 86.2)57.1 (44.9, 68.7)PFS rate at 12 months, % (80% CI)84.5 (74.1, 91.0)74.6 (59.4, 84.8)BICR, blinded independent central review; CI, confidence interval. Open table in a new tab